HUBUNGAN ANTARA BULLYING DENGAN HUBUNGAN SOSIAL SISWA DI SMP PGRI 7 SEDATI - Ardiansyah Diky Maulana; Dwi Nastiti; Ghozali Rusyid Affandi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Bullying is an experience commonly experienced by several children at school in the form of physical, verbal or psychological threats such as taunting, mocking, hitting or threatening a student victim by several students. Social relationships are relationships between humans who need each other in the form of interactions both between individuals and groups. This type of research is quantitative with the correlational method. The data collection technique is using a questionnaire. To determine the accuracy of the instrument, validity and reliability tests were carried out. The data analysis technique uses the korelational test, normality test, and linearity using SPSS 24. The sampling technique uses total sampling with the entire population being a sample of 48 students. The results of the study showed that the level of bullying experienced by students who were victims of bullying was 56.73%, while the level of social relations among students who were victims of bullying was 69.75% and the influence of bullying on the social relations of class VIII students at SMP PGRI 7 SEDATI was at a percentage of 0.371 or 37 .1% with a fairly strong classification.